Initial study for detection of multiple lymph nodes in the axillary region using Microwave Imaging - Eleutério, Ricardo (2022)
Breast cancer staging largely depends on the evaluation of whether there are cancer cells in the axillary lymph nodes. This work proposes a non-invasive method of detecting metastases in the lymph nodes using an Ultra-Wideband Microwave Imaging radar system. Energy profiles of the axilla are created with this system in which high energy regions may indicate the presence of metastasised lymph nodes.